DEFINING NEW POLICE AUTHORITIES IN LAW ON POLICE - Milidragović, Dragan; Milić, Nenad (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The advent of modern technologies and their implementation into various spheres of human activities, including security, allowed for a faster development of society, while increasing the risk of human rights violations. Therefore, a challenge arises of how to maximize the use of new technological features while still preserving citizen’s rights and freedoms. The application of measures, actions and tools in police work must be based on the law, or more precisely, on the adequate legal framework that is defined in the police authorities. Standardizing new police authorities is not an easy task and it requires coordination or finding a balance between security, law and human rights. This paper addresses this issue. Operational capabilities of modern technologies and other means that could find their use in police operations were analyzed and a precise standardized framework for their application has been proposed, by defining four new police authorities. In this paper, the idea of the authors was to point out the use and significance of the proposed new police authorities for future police work,  with the goal to implement them in the future law updates on Law on Police.
Keywords: police; police authorization; home or apartment entry; unmanned aerial vehicle; facial biometric pattern